Simple Global Ocean Biogeochemistry With Light, Iron, Nutrients and Gas Version 2 (BLINGv2): Model Description and Simulation Characteristics in GFDL's CM4.0. (29th September 2020) - Dunne, J. P.; Bociu, I.; Bronselaer, B.; Guo, H.; John, J. G.; Krasting, J. P.; Stock, C. A.; Winton, M.; Zadeh, N.
Abstract: Simulation of coupled carbon‐climate requires representation of ocean carbon cycling, but the computational burden of simulating the dozens of prognostic tracers in state‐of‐the‐art biogeochemistry ecosystem models can be prohibitive. We describe a six‐tracer biogeochemistry module of steady‐state phytoplankton and zooplankton dynamics in Biogeochemistry with Light, Iron, Nutrients and Gas (BLING version 2) with particular emphasis on enhancements relative to the previous version and evaluate its implementation in Geophysical Fluid Dynamics Laboratory's (GFDL) fourth‐generation climate model (CM4.0) with ¼° ocean. Major geographical and vertical patterns in chlorophyll, phosphorus, alkalinity, inorganic and organic carbon, and oxygen are well represented. Major biases in BLINGv2 include overly intensified production in high‐productivity regions at the expense of productivity in the oligotrophic oceans, overly zonal structure in tropical phosphorus, and intensified hypoxia in the eastern ocean basins as is typical in climate models. Overall, while BLINGv2 structural limitations prevent sophisticated application to plankton physiology, ecology, or biodiversity, its ability to represent major organic, inorganic, and solubility pumps makes it suitable for many coupled carbon‐climate and biogeochemistry studies including eddy interactions in the ocean interior. We further overview the biogeochemistry and circulation mechanisms that shape carbon uptake over the historical period. As an initial analysis of model historical and idealized response, we show that CM4.0 takes up slightly more anthropogenic carbon than previous models in part due to enhanced ventilation in the absence of an eddy parameterization. The CM4.0 biogeochemistry response to CO2 doubling highlights a mix of large declines and moderate increases consistent with previous models. Plain Language Summary: Cutting edge climate model development efforts often do not include representation of the carbon cycle and biogeochemical tracers due to the large computational expense of these additional tracers. During GFDL CM4.0 development, an effort was made to include a simple representation of these processes to explore ocean biogeochemistry at eddying resolution. This simple ocean biogeochemistry builds on the previous BLINGv1 effort (Galbraith et al., 2010, https://doi.org/10.5194/bg-7-1043-2010 ) and is suitable for carbon uptake and provides a computationally light means to simulate large‐scale patterns in ocean biogeochemical tracers. Key Points: A simple biogeochemistry module is described to simulate ocean phosphorus, iron, oxygen, organic and inorganic carbon, and alkalinity cycles This module has been run in a new climate model with quarter degree resolution ocean and compares well with observations This steady‐state ecosystem provides a computationally light means to simulate large‐scale patterns in ocean biogeochemical tracers